Imunoexpressão do EGFR e da podoplanina em cistos radiculares e dentígeros - Maia, Viviane Alves de Oliveira (2014)
The radicular cysts (RCs) and dentigerous (DCs), despite having different etiologies, form a pathological cavity lined by epithelium, which grows due to the buildup of fluid inside, as the surrounding bone is reabsorbed and the epithelium will being induced to proliferate. The epithelial proliferation, which has been identified as one of the key processes in the growth of odontogenic cystic lesions, is influenced by growth factors such as EGFR (epidermal growth receptor factor) and podoplanin (PDPN), many of which may have its production stimulated mainly during inflammatory processes. The objective of this research was to evaluate and compare the immunohistochemical expression of EGFR and PDPN in 30 cases of RCs and 30 cases of DCs, semiquantitatively, in light microscopy, associating it with the degree of inflammation, cellular localization of immunostaining and with the immunostained epithelial layers. Data were statistically analyzed by Chi-square test and Fisher exact test, considering a significance level of 5 %. The results showed high immunoreactivity of both proteins in the lesions studied, only statistically significant difference was observed in immunostaining of PDPN (p=0.033), which proved higher in RCs. The other analyzed parameters showed no relevant significant differences. We conclude that, as EGFR and PDPN showed high immunoreactivity in cystic lesions analyzed, these proteins participate the pathogenesis of these lesions through the epithelial stimulation process, despite having different etiologies. Furthermore, it can infer that the higher immunostaining of PDNP in RCs that DCs showed no distinction indicator between the two lesions, regarding their etiologies, once this protein also showed a considerable expression in DCs, independent of the intensity of the inflammatory infiltrate